Assessment of Treg-related lncRNAs in epilepsy - Sharifi, Guive; Eghtedarian, Reyhane; Taheri, Mohammad; Hussen, Bashdar Mahmud; Eslami, Solat; Ghafouri-Fard, Soudeh; Sayad, Arezou (Frontiers in Molecular Neuroscience, 2023)
Recent studies have shown dysregulation of several groups of long non-coding RNAs in the context of epilepsy. According to evidence regarding the role of regulatory T cells in this disorder, we examined expression levels of regulatory T cell-related lncRNAs, namely TH2-LCR, RMRP, IFNG-AS1 (NEST), MAFTRR and FLICR in the blood of epileptic cases compared with controls. Expression of RMRP was lower in patients with refractory epilepsy compared with controls [expression ratio (95% CI) = 0.32 (0.13–0.8), adjusted p-value = 0.0008]. Besides, its expression was lower in refractory patients vs. non-refractory patients [expression ratio (95% CI) = 0.2 (0.1–0.41), adjusted p-value < 0.0001]. Expression of TH2-LCR was lower in refractory patients vs. controls [expression ratio (95% CI) = 0.4 (0.17–0.93), adjusted p-value = 0.0044] and in refractory patients vs. non-refractory ones [Expression ratio = 0.28 (0.19–0.58), p-value < 0.0001]. Expression of NEST was higher in total patients [expression ratio (95% CI) = 2.48 (1.15–5.27), adjusted p-value = 0.0012] and in both groups of patients compared with controls. However, its expression was not different between refractory and non-refractory cases. Similarly, FLICR and MAFTRR were over-expressed in total cases and both groups of patients compared with controls, but their expressions were similar between refractory and non-refractory cases. MAFTRR could differentiate between total epileptic cases and controls with AUC value of 0.8. This lncRNA could separate refractory and non-refractory cases from healthy controls with AUC values of 0.73 and 0.88, respectively. This study provides evidence for deregulation of regulatory T cell-related lncRNAs in epilepsy and their potential role as diagnostic markers in this condition.